Permanent Pancreatic Duct Occlusion With Neoprene-based Glue Injection After Pancreatoduodenectomy at High Risk of Pancreatic Fistula: A Prospective Clinical Study. Issue 5 (November 2019) - Mazzaferro, Vincenzo; Virdis, Matteo; Sposito, Carlo; Cotsoglou, Christian; Droz Dit Busset, Michele; Bongini, Marco; Flores, Maria; Prinzi, Natalie; Coppa, Jorgelina
Abstract : Objective: The aim of this study was to assess safety and efficacy of pancreatic duct occlusion (PDO) with neoprene-based glue in selected patients undergoing pancreatoduodenectomy (PD) at high risk of postoperative pancreatic fistula (POPF). Background Data: PD is the reference standard approach for tumors of the pancreaticoduodenal region. POPF is the most relevant complication after PD. PDO has been proposed as an alternative to anastomosis to manage the pancreatic stump. Methods: A single-center, prospective, nonrandomized trial enrolled 100 consecutive PD for cancer. Patients at high risk for POPF according to Fistula Risk Score (FRS) >15% (≥6 points) were treated with PDO using neoprene glue (study cohort); patients with FRS ⩽15% (⩽5 points) received pancreaticojejunal anastomosis (PJA: control cohort). Primary endpoint was complication rate grade ≥3 according to Dindo–Clavien Classification (DCC). Other postoperative outcomes were monitored (ClinicalTrials.gov NCT03738787). Results: Fifty-one patients underwent PDO and 49 PJA. DCC ≥3, postoperative mortality, and POPF grade B-C were 25.5% versus 24.5% ( P = 0.91), 5.9% versus 2% ( P = 0.62), and 11.8% versus 16.3% ( P = 0.51) in the study versus control cohort, respectively. At 1 and 3 years, new-onset diabetes was diagnosed in 13.7% and 36.7% of the study cohort versu 4.2% and 12.2% in controls ( P = 0.007). Conclusions: PDO with neoprene-based glue is a safe technique that equalizes early outcome of selected patients at high risk of POPF to those at low risk undergoing PJA. Neoprene-based PDO, however, triples the risk of diabetes at 1 and 3 years. Abstract : Supplemental Digital Content is available in the text